PEMBUATAN MULTIMEDIA PEMBELAJARAN RESTORAN DAN BARISTA UNTUK MENINGKATKAN HASIL BELAJAR DAN KEAKTIFAN MAHASISWA PENDIDIKAN TATA BOGA MENGGUNAKAN ADOBE FLASH - Hamdani, Fahri; Sasmita Susanto, Eri; Yuliadi, Yuliadi; Aldrin, Aldrin (Badan Penelitian dan Pengabdian Masyarakat (BP2M) STMIK Syaikh Zainuddin NW Anjani, 2023)
This study objective to: (1) produce Adobe Flash-based learning multimedia for Culinary Education Students in restaurant and barista courses, (2) find out to what extent learning multimedia improves student learning outcomes, (3) find out to what extent learning multimedia improves student activity. The method used is Research and Development (R&D) with reference to the development steps of Alessi & Trollip. The test subjects of this study consisted of an alpha test and a beta test. Data collection on learning outcomes was carried out by giving a pre-test and post-test, while active data collection was carried out by assessing student activity when using multimedia. The results of the study show that: (1) multimedia products in the criteria are very feasible to use both in terms of aspects of material assessment and aspects of media assessment, (2) learning multimedia improves student learning outcomes with an achievement percentage of 5% (pre-test) to 91 .5% (post-test), (3) multimedia learning increases student activity by 66.90% with high criteria.